The impact of packaging colour on children's brand name memorization (7-12 years old). Issue 11 (25th November 2014) - de Faultrier, Brigitte; Bezaz, Nora
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the effect of packaging colour (chromatic vs achromatic) on children's brand name memorization (recall and recognition). This research examined the impact of age and school grade on brand name memorization and on the relationship between packaging colour and memorization. Design/methodology/approach – The experimentation concerned 160 French children from seven to 12 years old. Findings – The results showed that chromatic colour of packaging has a positive impact on brand name recognition but not on the recall. Furthermore, the age variable has a significant positive effect on recall capacity but not on brand name recognition. Research limitations/implications – Other variables can be introduced in the conceptual model, like product involvement (by adding other products), children's colour preference, hue and value colour (by included diverse colours). Practical implications – Children's importance as a commercial target is increasing, marketing managers have to differentiate their products on the shelves. Consequently, the choice of the packaging dominant colour appears to be a crucial strategic decision, because it allows children to recognize the brand name. Professionals have to adapt their strategies of differentiation to children's ages knowing that younger children need more visual stimuli than older ones. Originality/value – This research has important theoretical contributions. There is very little research on the effect of packaging on children's purchasing behaviour. Moreover, no research has studied the impact of colour packaging on children's memorization (seven to 12 years old).